2016
DOI: 10.1371/journal.pone.0168251
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Publication Status of Pediatric Liver Transplantation Studies

Abstract: IntroductionPediatric liver transplantation is a highly specialized, challenging field. Selective reporting may introduce bias into evidence based clinical decision making, but the precise extent of unpublished data in pediatric liver transplantation is unknown today. We therefore assessed the public availability of completed clinical trials in pediatric liver transplantation.MethodsWe determined the proportion of published and unpublished pre-registered, completed pediatric liver transplantation studies on Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
3
9
0
Order By: Relevance
“…Unfortunately, the low publication rate for studies on ED that we found in our analysis is in line with other published observations. Anderson et al recently reported that only 38.3% of all completed or prematurely terminated trials registered at ClinicalTrials.gov were published 15 , and we came to similar conclusions when testing for publication bias in fields as diverse as pediatric liver transplantation 16 or autism 17 . Publication of the results gathered in clinical trials involving human subjects is considered an ethical imperative 18 .…”
Section: Discussionsupporting
confidence: 81%
“…Unfortunately, the low publication rate for studies on ED that we found in our analysis is in line with other published observations. Anderson et al recently reported that only 38.3% of all completed or prematurely terminated trials registered at ClinicalTrials.gov were published 15 , and we came to similar conclusions when testing for publication bias in fields as diverse as pediatric liver transplantation 16 or autism 17 . Publication of the results gathered in clinical trials involving human subjects is considered an ethical imperative 18 .…”
Section: Discussionsupporting
confidence: 81%
“…Similar issues exist in other challenging areas of paediatric medicine, such as epilepsy, autism and liver transplantation. 15–17 22 …”
Section: Discussionmentioning
confidence: 99%
“…Selective reporting of clinical trial results introduces bias into evidence-based clinical decision-making. 15–17 The precise extent of bias in paediatric appendicitis is unknown. We therefore assessed the public availability of study results of completed clinical studies involving children with appendicitis registered in the major clinical trial database.…”
Section: Introductionmentioning
confidence: 99%
“…A trend towards improvement in terms of timely, pubic availability of results exists also in other areas of paediatric medicine, such as epilepsy, autism and liver transplantation, even if a considerable amount of study data from registered and completed studies is still missing today. 32–34 41 …”
Section: Discussionmentioning
confidence: 99%
“…As the current literature shows, however, unselective reporting of study results in paediatrics must still be considered. 32–34 …”
Section: Introductionmentioning
confidence: 99%